Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.onc.1206744
|View full text |Cite|
|
Sign up to set email alerts
|

Association of a lung tumor suppressor TSLC1 with MPP3, a human homologue of Drosophila tumor suppressor Dlg

Abstract: We have previously identified the tumor suppressor in lung cancer 1 (TSLC1) gene as a novel tumor suppressor in human non-small cell lung cancer (NSCLC) by functional complementation. TSLC1 encodes a membrane glycoprotein belonging to an immunoglobulin superfamily and participates in cell adhesion. A truncating mutation of the TSLC1 corresponding to its cytoplasmic domain in a primary NSCLC tumor suggests that this domain is important for tumor suppressor activity. Here, we report that TSLC1 directly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…We have demonstrated that protein4.1B/DAL-1, a member of the protein 4.1 family, connects TSLC1 to the actin cytoskeleton, and the interaction is involved in actin reorganization (9). Along with others, we have reported that TSLC1 also interacts with membrane-associated guanylate kinase homologs (MAGuKs) through its class II PDZ domain (6,7,10), implying that TSLC1, protein 4.1, and MAGuK form a tripartite complex. TSLC1 was originally identified based upon its ability to suppress tumorigenicity of human lung adenocarcinoma A549 cells in nude mice (2).…”
mentioning
confidence: 54%
“…We have demonstrated that protein4.1B/DAL-1, a member of the protein 4.1 family, connects TSLC1 to the actin cytoskeleton, and the interaction is involved in actin reorganization (9). Along with others, we have reported that TSLC1 also interacts with membrane-associated guanylate kinase homologs (MAGuKs) through its class II PDZ domain (6,7,10), implying that TSLC1, protein 4.1, and MAGuK form a tripartite complex. TSLC1 was originally identified based upon its ability to suppress tumorigenicity of human lung adenocarcinoma A549 cells in nude mice (2).…”
mentioning
confidence: 54%
“…Furthermore, the intracellular tails of the Cadms have been shown to interact with several scaffolding molecules in various in vitro systems. These include CASK (Biederer et al, 2002), syntenin (Biederer et al, 2002;Meyer et al, 2004), GRIP (Meyer et al, 2004), MPP3 (ortholog of the Drosophila tumor suppressor gene Dlg; Fukuhara et al, 2003), and DAL-1 (Yageta et al, 2002). However, very little is known about how these interactions relate to the functions of the Cadms during development.…”
Section: Introductionmentioning
confidence: 99%
“…The juxtamembrane region of the cytoplasmic tail contains a band 4.1-binding motif and binds the tumor suppressor DAL-1, a band 4.1 family member, which connects Necl-2 to the actin cytoskeleton (23). In addition, the cytoplasmic tail contains a PDZ domain-binding motif in its C-terminal region and binds Pals2, Dlg3/MPP3, and CASK, which are MAGUK subfamily members having an L27 domain (15,20,24,25). However, the exact roles of the binding of these molecules to Necl-2 remain unknown.…”
mentioning
confidence: 99%